Response to erythropoietic‐stimulating agents in patients with chronic myelomonocytic leukemia. (22nd October 2015) - Xicoy, Blanca; Germing, Ulrich; Jimenez, María‐José; Garcia, Olga; Garcia, Regina; Schemenau, Jeniffer; Pedro, Carme; Luño, Elisa; Bernal, Teresa; González, Bernardo; Strupp, Corinna; Ardanaz, Maite; et al.
Abstract: Background: The efficacy of erythropoietic‐stimulating agents (ESA) in chronic myelomonocytic leukemia (CMML) is unknown. Our objective was to analyze erythroid response (ER) and overall survival (OS) in a series of 94 patients with CMML treated with ESA. Methods: We analyzed a series of 94 patients with CMML treated with ESA included in the Spanish and Düsseldorf‐MDS registries. Findings: ER was observed in 64% of patients and red blood cell (RBC) transfusion independence in 31%. The median duration of ER was 7 months (range, 0–88). CPSS and EPO level were significantly associated with ER in multivariate analysis ( P = 0.003). Considering only patients with CPSS low‐ or intermediate‐1‐risk group, the absence of RBC transfusion dependence and erythropoietin (EPO) level predicted ER ( P = 0.003 and P = 0.008, respectively). In multivariate analysis, only the EPO level retained its prognostic value ( P = 0.029). Achievement of ER correlated with a better survival since ER evaluation ( P = 0.016). Interpretation: The CPSS and EPO levels are adequate tools to select CMML patients with symptomatic anemia who may benefit from treatment with ESA. A significant ER to ESA is expected in anemic patients with low/intermediate‐1 CMML risk by the CPSS and a low endogenous serum EPO level.